Distribution of Connective Tissue in the Male and Female Porcine Liver: Histological Mapping and Recommendations for Sampling - Mik, P; Tonar, Z; Malečková, A; Eberlová, L; Liška, V; Pálek, R; Rosendorf, J; Jiřík, M; Mírka, H; Králíčková, M; Witter, K (Journal of comparative pathology, 2018)
The pig is a large animal model that is often used in experimental medicine. The aim of this study was to assess, in normal pig livers, sexual dimorphism in the normal fraction of hepatic interlobular and intralobular connective tissue (CT) in six hepatic lobes and in three macroscopical regions of interest (ROIs) with different positions relative to the liver vasculature. Using stereological point grids, the fractions of CT were quantified in histological sections stained with aniline blue and nuclear fast red. Samples (415 tissue blocks) were collected from healthy piglets, representing paracaval, paraportal and peripheral ROIs. There was considerable variability in the CT fraction at all sampling levels. In males the mean fraction of interlobular CT was 4.7 ± 2.4% (mean ± SD) and ranged from 0% to 11.4%. In females the mean fraction of the interlobular CT was 3.6 ± 2.2% and ranged from 0% to 12.3%. The mean fraction of intralobular (perisinusoidal summed with pericentral) CT was <0.2% in both sexes. The interlobular CT represented >99.8% of the total hepatic CT and the fractions were highly correlated (Spearman r = 0.998, P <0.05). The smallest CT fraction was observed in the left medial lobe and in the paracaval ROI and the largest CT fraction was detected in the quadrate lobe and in the peripheral ROI. For planning experiments involving the histological quantification of liver fibrosis and requiring comparison between the liver lobes, these data facilitate the power analysis for sample size needed to detect the expected relative increase or decrease in the fraction of CT.
Keywords: játra; Swine; histology; Female; liver; Animals; connective tissue; ženské pohlaví; Liver; mužské pohlaví; Male; pig; zvířata; prasata; Connective Tissue; pojivová tkáň